Central African Republic : First Review of the Arrangement Under the Extended Credit Facility, Financing Assurances Review and Request for Waiver of Nonobservance of Performance Criterion. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2017)
This paper discusses Central African Republic's First Review of the Arrangement Under the Extended Credit Facility (ECF), Financing Assurances Review and Request for Waiver of Nonobservance of Performance Criterion (PCs). Program implementation through the end of August has been satisfactory. All quantitative and indicative targets were met, with the exception of the criterion on nonaccumulation of external payments for which the authorities are taking corrective measures. Improvement in tax revenue, albeit in line with the program target, remains fragile. The IMF staff supports completion of the first review under the ECF arrangement and the authorities' request for a waiver for the nonobservance of a PC. The IMF staff also recommends that the financing assurances review be completed.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet